Flexitarianism (Flexible or Part-Time Vegetarianism): A User-Based Dietary Choice for Improved Wellbeing - Raphaely, Talia; Marinova, Dora; Crisp, George; Panayotov, Jordan (International Journal of User-Driven Healthcare, 2014)
Many think that eating meat is nutritionally necessary and beneficial. Industrialising livestock production provides meat that is often “cheaper” than fruit and vegetables. In reality, this has come at a cost for human, animal and ecological welfare. Western mainstream meat consumption is a leading cause of increasing ill-health, diabetes, cancers, non-communicable and chronic diseases, malnourishment, obesity, antibiotic resistance, spread of infectious diseases, hunger and possible global epidemics as well as climate change, biodiversity loss, water and land degradation. Rather than stop this, vested interests continue to promote meat consumption. If people are deliberately misinformed or have no access to reliable information, what chance do they have to make the right food choices? This paper outlines flexitarianism (flexible vegetarianism) as a personal user-driven opportunity to combat the geopolitical and industrial duplicity about meat. Consumers should have enough information about the implications of their nutritional choices. In addition to health benefits, flexitarianism can help mitigate climate change, environmental and social destruction and reduce animal suffering. The proposed information policy interventions are assessed against their impact on key stakeholders and overall value for public health and environmental wellbeing. They offer an opportunity to reclaim personal health and improve the health of the planet.